Strategi Pengembangan Bisnis Produk Hortikultura Pada Waaida Farm: Developing business strategic of horticultura product in Waaida Farm - Uding Sastrawan; Rahmat Yanuar Ramadhaning; Maisya Nurrizky Az Zahra; Syarifah Annisaputri (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2016)
This study aims to determine alternative strategies in the business development of horticulture product in Waaidah Farm. Method used survey with SWOT analysis, Internal-External (IE) matrix and QSPM. The results show that the total value obtained from the IFAS table is 3.037 with a strength score of 2.556 and the weakness score of 0.481, it shows that the strength factor of the horticulture sector business is greather than the weakness factor,while the total value EFAS of 0.286, with a opportunity score of 2,500 and a threat of 0,286. This means that the opportunity factor is greather than the threat factor. The result of calculation of rating value and internal factor weight the business development strategy of horticulture product in Waaidah Farm with Internal-External (IE) matrix shows the position of Waaidah Farm in cell IV which means that this business must carry out a grow and build strategy. Based on SWOT analysis, there are 7 types of alternative strategies formed so that the priority strategy results using QSPM is establishment of ciplukan juice processing business unit with a TAS value of 6,364.